2017
DOI: 10.1007/s10126-017-9744-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Based Identification of the Desiccation Response Genes in Marine Red Algae Pyropia tenera (Rhodophyta) and Enhancement of Abiotic Stress Tolerance by PtDRG2 in Chlamydomonas

Abstract: Pyropia tenera (Kjellman) are marine red algae that grow in the intertidal zone and lose more than 90% of water during hibernal low tides every day. In order to identify the desiccation response gene (DRG) in P. tenera, we generated 1,444,210 transcriptome sequences using the 454-FLX platform from the gametophyte under control and desiccation conditions. De novo assembly of the transcriptome reads generated 13,170 contigs, covering about 12 Mbp. We selected 1160 differentially expressed genes (DEGs) in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, greater levels of desiccation are typically detrimental to photosynthesis. Seaweeds that are desiccation tolerant have various cellular mechanisms for rapidly repairing cellular membranes and metabolic processes upon rehydration (Burritt et al 2002;Im et al 2017;Kim et al 2009Kim et al , 2013Kumar et al 2011).…”
Section: Desiccationmentioning
confidence: 99%
“…However, greater levels of desiccation are typically detrimental to photosynthesis. Seaweeds that are desiccation tolerant have various cellular mechanisms for rapidly repairing cellular membranes and metabolic processes upon rehydration (Burritt et al 2002;Im et al 2017;Kim et al 2009Kim et al , 2013Kumar et al 2011).…”
Section: Desiccationmentioning
confidence: 99%
“…With respect to the life cycle, previous studies focused on characterization of the evolutionary aspects of the distinct stages [158,159], development of applied technologies including the designation of biomarkers [160], and treatments affecting the regulation of gene expression linked to reproductive processes [161]. A major focus for genomic research has been the interpretation and/or comparative analysis of transcriptomic data relating to the responses of laver species to abiotic stress [162,163], principally environmental conditions such as high temperature [164][165][166], repeated desiccation-rehydration [167,168], and hypersalinity [169].…”
Section: Future Issues: Identifying the Health-promoting Properties Omentioning
confidence: 99%
“…, Im et al. ). The role of HSPs in host–pathogen interaction has been extensively studied, and a defensive role against pathogens has been reported in some HSPs (Maimbo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous genome-wide expression studies showed that HSP groups are most prominently up-regulated genes in Pyropia species exposed to abiotic stresses (Choi et al 2013, Sun et al 2015. Several HSPs have been isolated from Pyropia species, and functional characterization using Chlamydomonas as an expression system confirmed their roles in enhancing tolerance against abiotic stress (Park et al 2012, Im et al 2017. The role of HSPs in host-pathogen interaction has been extensively studied, and a defensive role against pathogens has been reported in some HSPs (Maimbo et al 2007).…”
mentioning
confidence: 99%